If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3h=-5-(1/2)
We move all terms to the left:
-3h-(-5-(1/2))=0
We add all the numbers together, and all the variables
-3h-(-5-(+1/2))=0
We multiply all the terms by the denominator
-3h*2))-(-5-(+1=0
Wy multiply elements
-6h^2+1=0
a = -6; b = 0; c = +1;
Δ = b2-4ac
Δ = 02-4·(-6)·1
Δ = 24
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{24}=\sqrt{4*6}=\sqrt{4}*\sqrt{6}=2\sqrt{6}$$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{6}}{2*-6}=\frac{0-2\sqrt{6}}{-12} =-\frac{2\sqrt{6}}{-12} =-\frac{\sqrt{6}}{-6} $$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{6}}{2*-6}=\frac{0+2\sqrt{6}}{-12} =\frac{2\sqrt{6}}{-12} =\frac{\sqrt{6}}{-6} $
| c17=3 | | 12=5y+6 | | 7x+6(-3x+3)=-48 | | -2(3n-5)+5n=(6(n-3) | | -5b+14=-4b-9 | | 3(2z+1)=6z-2)+14 | | 3j=4/5 | | 12z-9z+-z-8z-10z=16 | | 23=5(x+5)-7x | | −2/3x+37=12 | | 5x+5=1x+9 | | 12z–9z+-z–8z–10z=16 | | 7x/2=20 | | 6x=x^2-4x+11 | | 5z-z-3z=3 | | 7(w+2)-1=6w+14 | | x+5/x-4+x-9/5x-4=1 | | 4m+m=20 | | 6((3r-5))/2+4=52 | | 12-1/2x=13 | | z/(1(2/9))=-27 | | 5x+4=3x-3 | | 11z=7 | | 6x–7=12 | | 16(3/4x-2)=8 | | 14p+3p+-18p+-15p=-16 | | 9x-142=83-6x | | 9=5x+14 | | –4y=-7 | | 13k-7k=18 | | (x-3)(x-7)=5 | | 3j=-3/5 |